Dynamics of software systems projects during the requirements process improvement. (18th December 2014) - Zawedde, Aminah; Williams, Ddembe
Requirements process improvement (RPI) in software systems is aimed at systematically controlling changes of the requirements specification and making improvements that result in high quality specifications at reduced costs and delivered within the specified schedule. RPI activities are dynamic and complex processes managing all changes to the requirements process. Therefore, in order to meet customer and business needs, organisations need to have an effective RPI that will result into quality specifications, within a stipulated budget. This paper explores the dynamics that exists among the factors that influence a successful RPI in order to provide the understanding required to explain how the underpinning process attributes affect the quality and associated costs of the RE specification delivered to the customer. The authors contend that the developed system dynamics based RPI model is a generic decision making framework for an effective approach to RPI.